Media Video Company Profile Sebagai Sarana Informasi Dan Promosi Di PT. Surya toto Indonesia Tbk. Kabupaten Tangerang - Erna Astriyani; Andri Lukmana; Agung Irawan (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2016)
The development of computer technology in particular fields of multimedia, visual and audio broadcasting already very rapidly growing at this time as well as the extent of the need for information on the society, the more recent contributions in presenting company profiles as both a media information and media promotion. PT. Surya Toto Indonesia Tbk. engaged in the manufacture of manufacture of sanitary, contributing to provide sanitary products, is an experienced company in the field of manufacturing and became one of the major companies in indonesia. PT. Surya Toto Indonesia now operates with two clean factory and factory pengepasan clean, and employs approximately 3.508 people. This dynamic company extends to a superior standard of product, market, highly motivated employees and the expansion of the sales network all over the world to provide quality products that improve our lives. With the aim to introduce the identity and overall information associated therein. PT. Surya Toto Indonesia certainly wants the effective presentation of information, accurate and interesting in terms of the look or content therein. The presentation of the information is packaged in the form of a video company profile is considered particularly useful for that purpose. Expected company profile video is worthwhile and could be implemented by PT Surya Toto Indonesia.